(untitled) - Kodansha Intanashonaru Kabushiki Kaisha (New York, 1995)
A generous selection of entries from this treasure trove of information have been reorganized into thematic sections such as geography, history, government and diplomacy, economy, society, culture, and life
Keywords: education - japan,japan - description and travel,japan - economic conditions,japan - history,japan - social aspects